2018
DOI: 10.1126/scitranslmed.aao4953
|View full text |Cite
|
Sign up to set email alerts
|

Opiates increase the number of hypocretin-producing cells in human and mouse brain and reverse cataplexy in a mouse model of narcolepsy

Abstract: The changes in brain function that perpetuate opiate addiction are unclear. In our studies of human narcolepsy, a disease caused by loss of immunohistochemically detected hypocretin (orexin) neurons, we encountered a control brain (from an apparently neurologically normal individual) with 50% more hypocretin neurons than other control human brains that we had studied. We discovered that this individual was a heroin addict. Studying five postmortem brains from heroin addicts, we report that the brain tissue had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 37 publications
7
105
2
1
Order By: Relevance
“…In Experiment 1, high motivation (low demand elasticity) animals had greater LH orexin expression than low motivation animals (high demand elasticity) animals. In Experiment 2, the number of remaining LH orexin cells following orexin-A morpholino antisense Although other studies reported that chronic exposure to drugs of abuse upregulated numbers of LH orexin-expressing cells (James, Stopper, Zimmer et al, 2018;Lawrence, Cowen, Yang et al, 2006;Thannickal, John, Shan et al, 2018), to our knowledge our results are the first to show a relationship between the endogenous number of LH orexin cells and baseline addiction propensity. Taken together, these results are consistent with our hypothesis that orexin signaling is particularly important in highly motivated individuals , and that the number of LH orexin neurons could serve as a biomarker of addiction susceptibility.…”
Section: High Motivation Animals Have Greater Orexin Expression In Lacontrasting
confidence: 46%
See 2 more Smart Citations
“…In Experiment 1, high motivation (low demand elasticity) animals had greater LH orexin expression than low motivation animals (high demand elasticity) animals. In Experiment 2, the number of remaining LH orexin cells following orexin-A morpholino antisense Although other studies reported that chronic exposure to drugs of abuse upregulated numbers of LH orexin-expressing cells (James, Stopper, Zimmer et al, 2018;Lawrence, Cowen, Yang et al, 2006;Thannickal, John, Shan et al, 2018), to our knowledge our results are the first to show a relationship between the endogenous number of LH orexin cells and baseline addiction propensity. Taken together, these results are consistent with our hypothesis that orexin signaling is particularly important in highly motivated individuals , and that the number of LH orexin neurons could serve as a biomarker of addiction susceptibility.…”
Section: High Motivation Animals Have Greater Orexin Expression In Lacontrasting
confidence: 46%
“…We reported that the persistent IntA-induced addiction phenotype was associated with higher numbers of orexin-expressing neurons in LH but not Pef/DMH (James, Stopper, Zimmer et al, 2018). Another recent study found that postmortem tissue from heroin addicts contains higher numbers of orexin-expressing neurons compared to healthy controls, and mice exposed to chronic non-contingent morphine injections had increases in the number of orexin neurons particularly in LH (Thannickal, John, Shan et al, 2018). These studies are consistent with an earlier study that reported that chronic alcohol consumption increased the area of prepro-orexin mRNA expression preferentially in LH of alcohol-preferring rats (Lawrence, Cowen, Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Indeed, we recently reported that the number and activity of orexin‐expressing neurons is higher in animals that exhibit high demand for cocaine following IntA (James et al ., ). Similarly, enhanced orexin expression has been reported in brains of human heroin addicts (Thannickal et al ., ) and in alcohol‐preferring rats following chronic alcohol intake (Lawrence et al ., ). Differences in orexin system function in high demand animals might also be associated with greater receptor densities in key reward regions or enhanced receptor binding; further studies are required to test these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Impact on the noradrenergic and/or serotonergic system could possibly explain this. However, a recent finding from Thannickal et al (2018) shed new light on the mode of action of opiates in narcolepsy. They discovered that human heroin addicts have, on average, 54% more hypocretinproducing cells than controls.…”
mentioning
confidence: 99%